Binder for lithium ion secondary battery negative electrode, slurry for forming lithium ion secondary battery negative electrode composite layer, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
The PPS/PEBA composite resin binder addresses the adhesion and volume change issues of high-capacity active materials in lithium-ion secondary batteries, improving cycle life and charging-discharge performance by forming a continuous structure that maintains lithium ion conductivity.
Patent Information
- Application Number
- JP2020172547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-13
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-10-13
AI Technical Summary
Conventional binders for lithium-ion secondary battery negative electrodes, such as polyvinylidene fluoride (PVDF) and styrene-butadiene rubber (SBR), fail to effectively manage the volume change of high-capacity active materials, leading to electrode peeling and reduced cycle life due to inadequate adhesion and interference with the formation of a stable solid electrolyte interface (SEI).
A composite resin binder composed of polyphenylene sulfide (PPS) and polyether block amide (PEBA) is used, forming a continuous structure that enhances adhesion between the negative electrode active material, conductive agent, and collector, thereby suppressing volume change and maintaining excellent charging and discharge characteristics.
The PPS/PEBA composite resin improves the cycle life and charging-discharge performance of lithium-ion secondary batteries by enhancing adhesion and maintaining lithium ion conductivity despite binder coverage of the active material surface.
Smart Images

Figure 0007625821000004 
Figure 0007625821000005 
Figure 0007625821000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder for a lithium ion secondary battery negative electrode, a slurry for forming a lithium ion secondary battery negative electrode mixture layer, a lithium ion secondary battery negative electrode, and a lithium ion secondary battery. [Background technology]
[0002] In recent years, lithium-ion secondary batteries have been widely used as power sources for electrical devices, etc. Furthermore, their use has recently expanded to include power sources for electric vehicles, and there is a demand for improved characteristics such as higher capacity, higher output, and improved cycle life, as well as high safety.
[0003] The negative electrode of a lithium-ion secondary battery has a structure in which a porous body consisting mainly of powdered negative electrode active material, a conductive additive, and a binder is layered and bound onto a current collector, and it is known that its performance is greatly affected not only by the properties of the negative electrode active material but also by the type of binder.
[0004] The negative electrode active material for lithium-ion secondary batteries is mainly made of carbon materials with a multilayer structure. In recent years, the development of high-capacity active materials has led to the use of silicon or tin, as well as their alloys and oxides.
[0005] Conventionally, polyvinylidene fluoride (PVDF) and styrene-butadiene rubber (SBR) have been the mainstream binders for negative electrodes. However, in electrodes using high-capacity active materials, the volume change associated with the absorption and release of lithium ions during charging and discharging is very large, and conventional binders are unable to suppress this volume change. As a result, peeling is likely to occur at the interface between the current collector and the active material layer, or the high-capacity active material itself becomes pulverized and is likely to fall off or peel off from the current collector, causing the electrode structure to collapse and resulting in a short charge-discharge cycle life for the battery.
[0006] As a method to address such problems, the use of polyimide resin or polyamideimide resin as a binder has been proposed (see, for example, Patent Documents 1 to 4). By using a polyimide resin or polyamideimide resin with specific mechanical properties as a binder for the negative electrode, it appears possible to absorb and mitigate the expansion and contraction of the negative electrode active material, thereby suppressing the deterioration of battery performance. However, there is a problem in that the active material is likely to be completely covered by the binder, which tends to inhibit the formation of a stable interface (SEI) on the negative electrode surface.
[0007] Furthermore, these polymers are not satisfactory in terms of adhesion to the current collector. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2004 / 004031 [Patent Document 2] Japanese Patent Application Publication No. 11-158277 [Patent Document 3] JP 2008-34352 A [Patent Document 4] JP 2000-200608 A Summary of the Invention [Problem to be solved by the invention]
[0009] In view of the above problems, an object of the present invention is to provide a binder for a negative electrode of a lithium ion secondary battery that enables the production of a negative electrode using a high-capacity active material with excellent cycle characteristics, as well as a slurry for forming a negative electrode composite layer for a lithium ion secondary battery using the binder, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Means for solving the problem]
[0010] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above object can be achieved by using a composite resin of polyphenylene sulfide (hereinafter sometimes referred to as PPS) and polyether block amide (hereinafter sometimes referred to as PEBA) blended in a specific composition as a negative electrode binder, and have thus completed the present invention.
[0011] That is, the respective aspects of the present invention are [1] to [4] shown below.
[0012] [1] A binder for a negative electrode of a lithium ion secondary battery, which binds a negative electrode active material, a conductive additive, and a current collector in the negative electrode of the lithium ion secondary battery, comprising a composite resin of polyphenylene sulfide and polyether block amide, the composite resin being made of a resin composition containing 55 to 75 mass % of polyphenylene sulfide and 25 to 45 mass % of polyether block amide, and wherein the polyphenylene sulfide and the polyether block amide form a co-continuous structure in a resin phase-separated structure observed with an electron microscope.
[0013] [2] A slurry for forming a negative electrode mixture layer for a lithium ion secondary battery, comprising: a negative electrode active material; a conductive assistant; the binder according to [1] above; and water.
[0014] [3] A negative electrode for a lithium ion secondary battery, comprising the binder according to [1] or [2] above.
[0015] [4] A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to [3] above.
[0016] The present inventors speculate as follows as to why the above object is achieved by the binder for a lithium ion secondary battery negative electrode of the present invention.
[0017] That is, in the present invention, by using a composite resin of polyphenylene sulfide and polyether block amide blended in a specific composition as a negative electrode binder, the following effects are exerted: the adhesion between the negative electrode active material or conductive assistant, and the current collector is improved; and the high mechanical strength of the composite resin of polyphenylene sulfide and polyether block amide makes it possible to suppress volumetric changes in the high-capacity active material. As a result, excellent charge / discharge characteristics and a long cycle life can be achieved.
[0018] Furthermore, since the composite resin of polyphenylene sulfide and polyether block amide has a bicontinuous structure, even if the surface of the active material is covered with a binder, a lithium ion conduction channel is secured, and excellent charge / discharge characteristics can be maintained. Effect of the Invention
[0019] According to the present invention, it is possible to provide a binder for a lithium ion secondary battery negative electrode that enables the production of a negative electrode using a high-capacity active material with excellent cycle characteristics, and a slurry for forming a lithium ion secondary battery negative electrode composite layer using the binder. Furthermore, by using the binder, it is possible to provide a lithium ion secondary battery negative electrode and a lithium ion secondary battery that have excellent charge / discharge characteristics and an extended cycle life. [Brief description of the drawings]
[0020] [Figure 1] The structure obtained by removing the PEBA component from the PPS / PEBA composite resin (C-1) obtained in Reference Example 1 [Diagram 2] The structure obtained by removing the PEBA component from the PPS / PEBA composite resin (C-3) obtained in Reference Example 3 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present invention will be described in detail below based on preferred embodiments thereof.
[0022] A binder for a negative electrode of a lithium ion secondary battery according to one embodiment of the present invention contains a composite resin of polyphenylene sulfide and polyether block amide.
[0023] Polyphenylene sulfide has a simple linear structure in which benzene rings and sulfur atoms are alternately bonded, and because it is a crystalline thermoplastic resin, it has high mechanical strength. In addition, because it has high fluidity when molten, it has an anchor effect that makes it excellent for bonding to metals.
[0024] The polyphenylene sulfide used in the present invention may have any of a linear structure, a branched structure, and a crosslinked structure, and preferably has a melt viscosity of 500 to 5,000 poise measured using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm under conditions of a measurement temperature of 315°C and a load of 10 kg.
[0025] Polyether block amide is a block copolymer of polyamide hard segments and polyether soft segments, and is a thermoplastic elastomer having a wide range of flexibility. Due to the presence of the polyether soft segments, it has lithium ion conductivity.
[0026] Examples of components of the polyether soft segment include glycol compounds such as polyethylene oxide glycol, polypropylene oxide glycol, polytetramethylene oxide glycol, and polyhexamethylene oxide glycol, as well as diamine compounds such as polyether diamine, etc. Two or more of these components may be used.
[0027] Examples of polyamide hard segments include nylon, specifically 6-nylon, 66-nylon, 610-nylon, 11-nylon, 12-nylon, 6 / 66 copolymer nylon, 6 / 610 copolymer nylon, 6 / 11 copolymer nylon, 6 / 12 copolymer nylon, 6 / 66 / 11 copolymer nylon, 6 / 66 / 12 copolymer nylon, 6 / 66 / 11 / 12 copolymer nylon, or 6 / 66 / 610 / 11 / 12 copolymer nylon. In this case, " / " is a symbol used to indicate that each nylon is a copolymer. For example, 6 / 66 copolymer nylon represents a copolymer nylon of 6-nylon and 66-nylon.
[0028] The polyether block amide used in the present invention preferably has a mass ratio of hard segment to soft segment of 70 / 30 to 30 / 70.
[0029] The polyether soft segment has a high swelling property in the electrolyte and therefore needs to be lowered to less than 70 mass %, but needs to be higher than 30 mass % in order to ensure lithium ion conductivity.
[0030] The method for compounding polyphenylene sulfide and polyether block amide is not particularly limited, and can be obtained by solution blending or melt kneading. Carbon nanotubes or inorganic fillers may be added during compounding.
[0031] It is preferable that the polyphenylene sulfide and the polyether block amide are composited in a mass ratio of 55 / 45 to 75 / 25.
[0032] Only at this composition ratio is a co-continuous structure formed, in which polyphenylene sulfide forms a network structure, and this structure makes it possible to achieve both the mechanical properties of polyphenylene sulfide and the lithium ion conductivity of polyether block amide, thereby achieving the object of the present invention. If the polyphenylene sulfide and polyether block amide are outside this range, the domain structure becomes a sea-island structure, and the co-continuous structure is no longer formed, which is not preferable.
[0033] There is no particular restriction on the average particle size of the composite resin of polyphenylene sulfide and polyether block amide, but the average particle size is preferably 1 to 10 μm.
[0034] The binder for a lithium ion secondary battery negative electrode of the present invention may consist only of a composite resin of polyphenylene sulfide and polyether block amide. However, when other binder components are contained, the content of the composite resin of polyphenylene sulfide and polyether block amide is preferably 15 mass % or more of the solid content of the slurry for forming the negative electrode composite layer.
[0035] The blending amount of the binder is preferably 10 to 30 mass %, and more preferably 15 to 25 mass %, based on the total amount of the negative electrode active material, the binder, and the conductive assistant.
[0036] In the present invention, the negative electrode active material that can be mixed into the negative electrode composite layer forming slurry is not particularly limited, but examples thereof include natural graphite, artificial graphite, graphite, mesocarbon microbeads (MCMB), tin and / or tin alloy, tin oxide, silicon and / or silicon alloy, silicon oxide, etc. In addition, when the negative electrode active material is an alloy, the negative electrode active material may contain a material that is alloyed with lithium. In addition, examples of the material that is alloyed with lithium include germanium, tin, lead, zinc, magnesium, sodium, aluminum, gallium, indium, and alloys thereof. However, in order to increase the battery capacity in the negative electrode, the negative electrode active material is preferably silicon and / or silicon alloy, silicon oxide, and particularly preferably silicon. In addition, a plurality of negative electrode active materials may be mixed. When the negative electrode active material is particulate, its average particle size is not particularly limited, but is preferably 5 μm or more and 20 μm or less. If the particle size of the negative electrode active material particles is less than 5 μm, the surface area of the negative electrode active material particles per unit mass increases, the contact area with the nonaqueous electrolyte increases, and irreversible reactions increase, leading to a decrease in capacity, which is not preferable. On the other hand, if the average particle size exceeds 20 μm, the resistance between the negative electrode active material particles and the negative electrode current collector is reduced, but the negative electrode active material particles are easily peeled off from the negative electrode current collector due to the stress caused by the volume change of the negative electrode active material particles during charging and discharging, which is not preferable.
[0037] There is no particular restriction on the conductive assistant contained in the negative electrode, and any electronically conductive material that does not adversely affect the battery characteristics can be used. Specifically, examples of the conductive assistant include conductive carbon such as Ketjen black and acetylene black, natural graphite, artificial graphite, carbon whiskers, carbon nanotubes, carbon fiber powder, and other carbon materials, metal powders and metal fibers such as Cu, Fe, Ag, Ni, Pd, Au, Pt, In, and W, and conductive metal oxides such as indium oxide and tin oxide. The blending amount of these conductive assistants is preferably 1 to 30% by mass with respect to the negative electrode active material.
[0038] The slurry for forming the negative electrode composite layer of the lithium ion secondary battery, which is one aspect of the present invention, contains the binder, the negative electrode active material, the conductive assistant, and water. The slurry may contain a viscosity adjuster such as carboxymethyl cellulose, or a pH adjuster such as an acid or an alkali, if necessary. The solid content concentration of the slurry is not particularly limited, but is preferably 20 to 80 mass % in consideration of the viscosity of the slurry, the dispersibility of the solid content, the load on the drying process, and the like. The ratio of the solid content in the slurry is preferably negative electrode active material: conductive assistant: binder = 20 to 98: 1 to 30: 1 to 50 by mass ratio. There is also no particular limitation on the method for producing the slurry, and examples thereof include a method in which the binder, the negative electrode active material, and the conductive assistant are mixed and dispersed in water all at once to prepare a slurry, a method in which the binder is first dispersed in water, and then the negative electrode active material and the conductive assistant are added to the binder aqueous solution and mixed to prepare a slurry, and a method in which the negative electrode active material and the conductive assistant are first mixed, and then mixed with the binder dispersion. There are also no particular limitations on the mixer used to prepare the slurry, and a mortar, roll mill, ball mill, screw mill, vibration mill, homogenizer, planetary centrifugal mixer, etc. may be used.
[0039] The negative electrode for lithium ion secondary battery according to one embodiment of the present invention contains the binder. Such a negative electrode for lithium ion secondary battery is preferably composed of a negative electrode current collector and a negative electrode mixture layer obtained by applying the slurry onto the negative electrode current collector and drying the slurry. The thickness of the negative electrode mixture layer containing the negative electrode active material, the binder, and the conductive assistant is preferably 10 to 200 μm.
[0040] The negative electrode current collector preferably has a surface roughness Ra of 0.1 μm or more. When a negative electrode mixture layer is formed on a negative electrode current collector having a surface roughness Ra of 0.1 μm or more, the binder has a large anchor effect in the negative electrode mixture layer, and the adhesion between the negative electrode current collector and the negative electrode mixture layer is greatly improved.
[0041] The material of the negative electrode current collector may be a conductor whose surface in contact with the negative electrode mixture layer exhibits electrical conductivity, and examples thereof include metals such as copper, nickel, iron, titanium, and cobalt, and alloys thereof. In particular, a metal foil containing copper is preferred, and copper foil or copper alloy foil is more preferred. The metal foil containing copper may be a metal foil made of a metal element other than copper, on the surface of which a layer containing copper is formed.
[0042] In the present invention, the thickness of the negative electrode current collector is not particularly limited, but is usually in the range of 10 μm to 100 μm.
[0043] There is no particular restriction on the manufacturing method of the negative electrode for lithium ion secondary batteries, and the negative electrode can be manufactured by applying the above-mentioned slurry onto a negative electrode current collector and drying it. There is no particular restriction on the method of applying the slurry, and methods such as slit coating, die coating, roll coating, dip coating, blade coating, knife coating, and wire bar coating can be used. There is no particular restriction on the drying method and conditions, and a normal hot air circulation type dryer, reduced pressure dryer, infrared dryer, or microwave heating dryer can be used. There is no particular restriction on the heating temperature, and the negative electrode can be heated and dried at 50 to 150°C.
[0044] Furthermore, by heating the negative electrode to 200 to 300°C after drying, the polyphenylene sulfide melts and flows, and the anchor effect strengthens the adhesion between the negative electrode mixture layer and the negative electrode current collector. Pressing the negative electrode under pressure also makes the porous structure uniform.
[0045] The lithium ion secondary battery according to one embodiment of the present invention is characterized by having the above-mentioned negative electrode for lithium ion secondary batteries. By using the above-mentioned negative electrode for lithium ion secondary batteries, a high-performance lithium ion secondary battery having excellent charge / discharge characteristics and a long cycle life can be provided. A lithium ion secondary battery is generally composed of a positive electrode, a negative electrode, a separator, a non-aqueous electrolyte, and the like. The negative electrode is a structure in which the above-mentioned negative electrode active material is bound to a negative electrode current collector by a binder together with the above-mentioned conductive assistant, and a negative electrode mixture layer containing the negative electrode active material, the binder, and the conductive assistant is formed on the current collector. The positive electrode also has a similar structure to the negative electrode, and is a structure in which the following positive electrode active material and the above-mentioned conductive assistant are bound to a positive electrode current collector by a binder. A porous film such as polyolefin is generally used as the separator, and is sandwiched between the positive electrode and the negative electrode to perform a shutdown function when the battery goes into thermal runaway. The non-aqueous electrolyte is a solution of an electrolyte salt such as LiPF6 in an organic solvent such as cyclic carbonate. The inside of the battery is filled with a non-aqueous electrolyte, and lithium ions move from the positive electrode to the negative electrode during charging, and move from the negative electrode to the positive electrode during discharging.
[0046] The positive electrode used in the lithium ion secondary battery of the present invention is not particularly limited, and can be made of known materials. The positive electrode is composed of a positive electrode mixture layer containing a positive electrode active material, a conductive additive, and a binder, and a current collector.
[0047] Any material that can insert and remove lithium ions can be used as the positive electrode active material. For example, transition metal oxides such as CuO, Cu2O, MnO2, MoO3, V2O5, CrO3, Fe2O3, Ni2O3, and CoO3, and Li X CoO2, Li X NiO2, Li X MnO2, Li X Mn2O4, LiNi X Co (1-X) O2, LiNi X Mn (2-X) O4, LiMn a Ni b Co cAmong these, a composite oxide of lithium and at least one transition metal selected from transition metals such as Co, Ni, and Mn is preferred, and specific examples thereof include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi X Co (1-X) O2, LiNi X Mn (2-X) O4, LiMn a Ni b Co c O2 (a+b+c=1). These lithium composite oxides may be doped with a small amount of elements such as fluorine, boron, Al, Cr, Zr, Mo, and Fe, or the surface of the lithium composite oxide particles may be surface-treated with carbon, MgO, Al2O3, SiO2, or the like.
[0048] As the conductive assistant for the positive electrode, the same conductive assistant as the conductive assistant exemplified for the negative electrode can be used.
[0049] As the binder for the positive electrode, a known binder may be used, and examples of the binder that can be used include fluorine-based resins such as polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, perfluoromethylvinyl ether-tetrafluoroethylene copolymer, polytetrafluoroethylene, and fluorine rubber; hydrocarbon elastomers such as styrene-butadiene copolymer and ethylene-propylene copolymer; polysaccharides such as carboxymethyl cellulose, alginic acid, and sodium alginate; and polyimides.
[0050] The positive electrode current collector may be a conductor whose surface in contact with the positive electrode composite layer exhibits electrical conductivity, and examples of the conductor include metals such as copper, gold, aluminum, titanium, nickel, stainless steel, or alloys thereof, conductive metal oxides such as indium oxide and tin oxide, and conductive materials such as conductive carbon. There is no particular restriction on the shape of the positive electrode current collector, and shapes such as foil, film, sheet, net, expanded metal, punched metal, and foam can be used. There is also no particular restriction on the thickness of the positive electrode current collector, and it is preferably about 1 to 100 μm.
[0051] There are no particular limitations on the non-aqueous electrolyte, and any known material can be used. The non-aqueous electrolyte is obtained by dissolving an electrolyte salt in an organic solvent. Examples of the electrolyte salt include CF3SO3Li, (CF3SO2)2NLi, (CF3SO2)2CLi, LiBF4, LiB(C6H8)4, LiPF4, LiClO4, LiAsF6, LiCl, and LiBr. Examples of the organic solvent for dissolving the electrolyte salt include ethylene carbonate, vinylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, γ-butyrolactone, tetrahydrofuran, 1,4-dioxane, anisole, diethyl ether, sulfolane, methylsulfolane, acetonitrile, propionitrile, butyronitrile, valeronitrile, benzonitrile, dimethylformamide, dimethylsulfoxide, trimethyl phosphate, triethyl phosphate, etc. The concentration of the electrolyte salt in the nonaqueous electrolyte can be selected in the range of 0.1 to 5 mol / L, preferably 0.5 to 3 mol / L.
[0052] There are no particular limitations on the separator, and any known separator can be used. Examples of the separator include a polyethylene microporous film, a polypropylene microporous film, a laminate of a polyethylene microporous film and a polypropylene microporous film, and a nonwoven fabric made of polyester fiber, aramid fiber, glass fiber, or the like. EXAMPLES
[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Polyphenylene sulfide and polyether block amide used in the production of a composite resin of polyphenylene sulfide and polyether block amide Details are shown below. <Polyphenylene sulfide (A)> Poly(p-phenylene sulfide) (A-1) (hereinafter simply referred to as PPS (A-1)) : Melt viscosity 2,070 poise. <Polyether block amide (B)> Polyether-polyamide block copolymer (B-1) (hereinafter referred to simply as PEBA (B-1)) : PEBAX MV1074 manufactured by Arkema Co., Ltd. (a block copolymer with a weight ratio of polyethylene oxide and polyamide 12 of 55 / 45) <Production of composite resin of polyphenylene sulfide and polyether block amide> (Reference example 1) (Production of PPS / PEBA composite resin (C-1)) PPS (A-1) 60% by mass and PEBA (B-1) 40% by mass were mixed and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 265° C. The resin components were melt-kneaded at a resin component discharge rate of 2.7 kg / hr, a screw speed of 200 rpm, and a set resin temperature of 270° C. The molten composition flowing out of the die was cooled and then cut to produce a pellet-shaped polyphenylene sulfide-polyether block amide composite resin (C-1). (Reference example 2) (Production of PPS / PEBA composite resin (C-2)) PPS (A-1) 70% by mass and PEBA (B-1) 30% by mass were mixed and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 270° C. The resin components were melt-kneaded at a resin component discharge rate of 2.6 kg / hr, a screw speed of 200 rpm, and a set resin temperature of 272° C. The molten composition flowing out of the die was cooled and then cut to produce a pellet-shaped polyphenylene sulfide-polyether block amide composite resin (C-2). (Reference example 3) (Production of PPS / PEBA composite resin (C-3)) PPS (A-1) 80% by mass and PEBA (B-1) 20% by mass were mixed and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 280° C. The resin components were melt-kneaded at a resin component discharge rate of 2.0 kg / hr, a screw speed of 200 rpm, and a set resin temperature of 285° C. The molten composition flowing out of the die was cooled and then cut to produce a pellet-shaped polyphenylene sulfide-polyether block amide composite resin (C-3). (Reference example 4) (Production of PPS / PEBA composite resin (C-4)) PPS (A-1) 90% by mass and PEBA (B-1) 10% by mass were mixed and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 280° C. The resin components were melt-kneaded at a resin component discharge rate of 2.2 kg / hr, a screw speed of 200 rpm, and a set resin temperature of 285° C. The molten composition flowing out of the die was cooled and then cut to produce a pellet-shaped polyphenylene sulfide-polyether block amide composite resin (C-4). (Reference example 5) (Production of PPS / PEBA composite resin (C-5)) PPS (A-1) 50% by mass and PEBA (B-1) 50% by mass were mixed and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 265° C. When melt-kneaded at a resin component discharge rate of 2.8 kg / hr, a screw rotation speed of 200 rpm, and a set resin temperature of 270° C., the molten composition flowing out of the die did not form strands, so the production of pellet-shaped polyphenylene sulfide-polyether block amide composite resin (C-5) was abandoned.
[0054] [Table 1]
[0055] <Observation of phase separation structure> The strands obtained during the manufacturing process of the PPS / PEBA composite resins (C-1 to C-4) were heated in N-methyl-2-pyrrolidone at 145°C for 2 hours to remove the PEBA component. The strand pieces that were left with only the PPS skeleton were observed using a tabletop microscope, Hitachi High-Technologies Corporation's Miniscope (registered trademark) TM3030Plus.
[0056] The PPS / PEBA composite resin (C-1), which was mixed with 60% by mass of PPS (A-1) and 40% by mass of PEBA (B-1), was observed to form a mesh-like skeleton, confirming that it had a bicontinuous structure.
[0057] In the PPS / PEBA composite resin (C-3) containing 80% by mass of PPS (A-1) and 20% by mass of PEBA (B-1), small holes were observed in the PPS matrix, confirming that it had an islands-in-a-sea structure.
[0058] <Evaluation of electrolyte swelling> PPS / PEBA composite resin (C-1 to C-4) press sheets measuring 5 cm square and 50 μm thick were prepared at a heating temperature of 300°C and a press pressure of 10 tons. They were then punched out to a diameter of 15 mm and immersed in an electrolyte solution with a volume ratio of ethylene carbonate / propylene carbonate of 1 / 1 for 3 days. The mass change rate after the immersion was measured to evaluate the swelling property. The mass change rate (%) is calculated by subtracting the mass before immersion in the electrolyte from the mass after immersion in the electrolyte, dividing the result by the mass before immersion in the electrolyte, and multiplying the result by 100.
[0059] <Lithium ion conductivity measurement> The PPS / PEBA composite resin (C-1 to C-4) press sheets prepared above were punched out to Φ15 mm and impregnated with an electrolyte containing 1 mol / L lithium hexafluorophosphate (ethylene carbonate / propylene carbonate = 1 / 1 volume ratio), and a cell was assembled in a glove box using a Toyo System bipolar cell. Lithium ion conductivity was measured using a Hioki Chemical Impedance Meter 3532-80 at an amplitude of ±10 mV and a measurement frequency range of 1 MHz to 4 Hz.
[0060] [Table 2]
[0061] <Coin cell manufacturing> The coin cells were designed and fabricated to have a high capacity of 930 mAh / cc or more by using 19.4 parts by mass or more of SiO.
[0062] Example 1 First, a negative electrode mixture was prepared from the following materials to fabricate a negative electrode. Negative electrode active material: 42.2 parts by mass of graphite (Gr: CGB-10 manufactured by Nippon Graphite Co., Ltd.), 25.8 parts by mass of silicon monoxide (SiO: manufactured by Osaka Titanium Co., Ltd.) Conductive assistant: 1 part by weight of acetylene black (AB: Denka Li-400) Thickener: 1 part by weight of carboxymethyl cellulose (CMC: Daicel Miraize #2200) Binder: 30 parts by mass of PPS / PEBA composite resin (C-1).
[0063] Gr, SiO, AB, and PPS / PEBA composite resin (C-1) were mixed, and then mixed with a CMC aqueous solution to prepare a slurry for forming a negative electrode composite layer. The slurry was then applied onto a copper foil using a bar coater and dried at 80°C for 10 minutes. After heat treatment at 300°C for 10 minutes, the mixture was pressed at 100°C under a load of 10 tons to prepare a negative electrode.
[0064] The adhesion of the resulting negative electrode was evaluated by scratching with a spatula and measuring the amount of the negative electrode mixture layer that peeled off from the copper foil. The electrode did not peel off and had a strong adhesion.
[0065] Next, a coin cell was produced using the obtained negative electrode as follows. That is, a lithium metal foil was used as the counter electrode, and lithium hexafluorophosphate was dissolved in an ethylene carbonate / dimethyl carbonate (1 / 1) mixed solvent to a concentration of 1 mol / L to prepare an electrolyte. A polyolefin microporous film (SD20B manufactured by WSCOPE) was used as the separator. The negative electrode and the counter electrode were then placed on both sides of the separator, stacked, and the electrolyte was poured in to produce a 2032-type coin cell.
[0066] Example 2 A coin cell was produced in the same manner as in Example 1, except that Gr was changed to 53.8 parts by mass, SiO was changed to 24.2 parts by mass, and the PPS / PEBA composite resin (C-1) was changed to 20 parts by mass.
[0067] Example 3 A coin cell was produced in the same manner as in Example 1, except that Gr was changed to 30.2 parts by mass, SiO was changed to 27.8 parts by mass, and the PPS / PEBA composite resin (C-1) was changed to 40 parts by mass.
[0068] Example 4 A coin cell was produced in the same manner as in Example 1, except that Gr was changed to 17.8 parts by mass, SiO was changed to 30.2 parts by mass, and the PPS / PEBA composite resin (C-1) was changed to 50 parts by mass.
[0069] Example 5 A coin cell was produced in the same manner as in Example 1, except that the PPS / PEBA composite resin (C-2) obtained in Reference Example 2 was used as the binder.
[0070] Comparative Example 1 A coin cell was produced in the same manner as in Example 1, except that styrene butadiene rubber (manufactured by JSR) was used as the binder, and Gr was changed to 77.6 parts by mass, SiO to 19.4 parts by mass, and SBR to 1 part by mass.
[0071] Comparative Example 2 A coin cell was produced in the same manner as in Example 1, except that the PPS / PEBA composite resin (C-3) obtained in Reference Example 3 was used as the binder.
[0072] Comparative Example 3 A coin cell was produced in the same manner as in Example 1, except that the PPS / PEBA composite resin (C-4) obtained in Reference Example 4 was used as the binder.
[0073] <Charge / discharge characteristic evaluation> The coin cells obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were used to evaluate the charge / discharge characteristics under the following conditions. Charging: Constant current constant voltage (CCCV mode) Discharge: Constant current (CC mode) Potential range: 0.05~2.0V C rate: 0.05C
[0074] [Table 3] [Industrial Applicability]
[0075] As described above, according to the present invention, it is possible to provide a binder for a lithium ion secondary battery negative electrode that enables the production of a negative electrode using a high-capacity active material with excellent cycle characteristics, and a slurry for forming a lithium ion secondary battery negative electrode composite layer using the same. Furthermore, by using the same, it is possible to provide a lithium ion secondary battery negative electrode and a lithium ion secondary battery that have excellent charge / discharge characteristics and extended cycle life.
Claims
1. A binder for a negative electrode of a lithium ion secondary battery, which binds a negative electrode active material, a conductive assistant, and a current collector in the negative electrode of the lithium ion secondary battery, comprises a composite resin of polyphenylene sulfide and a polyether block amide constituted of 30 to 70 mass % of a polyamide hard segment and 30 to 70 mass % of a polyether soft segment, the composite resin being made of a resin composition containing 55 to 75 mass % of polyphenylene sulfide and 25 to 45 mass % of polyether block amide, and the polyphenylene sulfide and the polyether block amide form a co-continuous structure in a resin phase separation structure observed with an electron microscope.
2. A slurry for forming a negative electrode mixture layer for a lithium ion secondary battery, comprising a negative electrode active material, a conductive assistant, the binder according to claim 1, and water.
3. A negative electrode for a lithium ion secondary battery, comprising the binder according to claim 1 .
4. A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 3.
Citation Information
Patent Citations
Binder resin for battery electrode and its production
JP1999158277A
Nonaqueous electrolyte secondary battery
JP2000106185A
Nonaqueous-electrolyte secondary battery
JP2000200608A
Lithium secondary cell and fabrication method thereof
JP2008034352A
Crystalline resin composition
JP2008189900A